THE INTEGRATION OF PHILOSOPHY IN THE DEVELOPMENT OF ISLAMIC RELIGIOUS EDUCATION CURRICULUM: AN EPISTEMOLOGICAL AND APPLIED ANALYSIS - Ciptadi, Teguh; Tobroni, Tobroni (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
Background: This research stems from the need to enhance Islamic Education in Indonesia by integrating philosophy, promoting critical thinking, and strengthening students' religious identity in a rapidly changing global landscape. Purpose: This study analyzes the integration of philosophy into the development of the Islamic Education curriculum from an epistemological perspective and its application in the context of education in Indonesia. The research aims to identify how the integration of philosophy can enrich the Islamic Education curriculum, enhance students' critical and reflective thinking skills, and strengthen their Islamic identity amidst the challenges of globalization. Method: Using a qualitative research method with a case study approach, the study finds that philosophy has significant potential to deepen religious understanding and develop students' intellectual and spiritual maturity. Result: However, the implementation of philosophical integration into the Islamic Education curriculum faces several challenges, including the intellectual readiness of students, the need for professional training for educators, and the necessity of clear guidelines for its application. Conclusion: The study concludes that with appropriate support, the integration of philosophy can play a crucial role in shaping students who not only possess a strong religious understanding but also the ability to think critically and participate in global dialogue. The implications of this research emphasize the importance of a more dynamic and reflective approach in Islamic religious education to address contemporary challeng